Ethyl 1-sec-butyl-2-phenyl-1H-benzimidazole-5-carboxylate - Arumugam, Natarajan; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Hemamalini, Madhukar; Fun, Hoong-Kun (International Union of Crystallography, 2010)
In the title molecule, C20H22N2O2, the benzimidazole ring system is essentially planar, with a maximum deviation of 0.024 (1) A ˚ . The dihedral angle between the phenyl and benzimidazole ring system is 43.71 (5). The atoms of the butyl group are disordered over two sets of sites with occupancies of 0.900 (4) and 0.100 (4). In the crystal structure, molecules are connected by weak intermolecular C—H O hydrogen bonds, forming chains along the b axis. The crystal structure is further stabilized by C—H interactions.